Effect of Ag loading on the adsorption/desorption properties of ZSM-5 towards toluene; Reaction Kinetics, Mechanisms and Catalysis; Vol. 119, iss. 2 - Temerev V. L. Victor; Vedyagin A. A. Aleksey Anatolievich; Afonasenko T. N. Tatyana; Iost K. N. Kristina; Kotolevich Yu. S. Yulia; Baltakhinov V. P. Vladimir; Tsyrulnikov P. G. Pavel (2016, 2016)
Title screen